Preparing for Classroom Activating Teaching Methods during Teacher Education in Finland - Xue, Lingling (fi=Turun yliopisto|en=University of Turku|, 2017)
Many researchers have asserted that all learning is inherently active, and national reports have clearly demonstrated the need for active learning in the classroom. Therefore, it is important for teachers to learn and use activating methods to stimulate students' active thinking and learning. This article investigates the activating methods that professional educators teach to their student teachers during the training period, and how student teachers apply these activating methods in practical ways in training schools during their practice period. Interviews were conducted among five teacher educators from the Faculty of Teacher Education at a university in Finland. Additionally, observations among 10 student teachers in total 52 classes were conducted at the regional teacher training school. The results indicated that most of the student teachers successfully applied activating teaching methods which were related to students’ higher order thinking skills during their training period. And activating teaching methods are helpful for teachers to apply in the classroom for activating students’ higher order thinking and learning.